Integrating Cardiology for Nuclear Medicine Physicians A Guide to Nuclear Medicine Physicians - Movahed, Assad.; Gnanasegaran, Gopinath.; Buscombe, John.; Hall, Margaret. (Springer Berlin Heidelberg, 2009)
Nuclear cardiology is no longer a medical discipline residing solely in nuclear medicine. This is the first book to recognize this fact by integrating in-depth information from both the clinical cardiology and nuclear cardiology literature, and acknowledging cardiovascular medicine as the fundamental knowledge base needed for the practice of nuclear cardiology. The book is designed to increase the practitioner's knowledge of cardiovascular medicine, thereby enhancing the quality of interpretations through improved accuracy and clinical relevance.The text is divided into four sections covering all major topics in cardiology and nuclear cardiology: Basic Sciences and Cardiovascular Diseases Conventional Diagnostic Modalities Nuclear Cardiology Management of Cardiovascular Diseases